Dry turning of AISI D3 steel using a mixed ceramic insert: A study. (October 2019) - Rath, D; Panda, S; Pal, K
AISI D3 steel is a new kind of hardened tool steel with excellent wear resistance. This hard material receives wide promotion, investigation, and application in the die manufacturing industries. In the machining of AISI D3 steel, tool wear has a close relationship with the presence of different constituent elements in the workpiece material and cutting conditions. This study reports an improved experimental investigation approach to the analysis of effect of cutting speed, feed rate, and depth of cut on cutting forces, surface roughness, tool wear, and chip morphology in high-speed turning of AISI D3 steel using a hybrid TiN-coated Al2 O3 + TiCN mixed ceramic insert. The range of each parameter is set at different levels for the analysis purpose. The experimental observations show that the cutting force is predominantly influenced by the feed rate accompanied by the depth of cut. The predominant factor influencing flank wear is the feed rate accompanied by the depth of cut and cutting speed. Feed rate is one of the dominating factors that influences the surface finish characteristics. The characterization of tool wear and chip morphology was performed by a scanning electron microscope supplied with energy-dispersive X-ray spectroscopy pattern. The results demonstrated that the predominant wear mechanism of the multilayered hybrid-coated tool was flank wear, crater wear, adhesion wear, and abrasive wear.